2023
DOI: 10.3390/ijms24076368
|View full text |Cite
|
Sign up to set email alerts
|

Recent Theoretical Insights into the Oxidative Degradation of Biopolymers and Plastics by Metalloenzymes

Abstract: Molecular modeling techniques have become indispensable in many fields of molecular sciences in which the details related to mechanisms and reactivity need to be studied at an atomistic level. This review article provides a collection of computational modeling works on a topic of enormous interest and urgent relevance: the properties of metalloenzymes involved in the degradation and valorization of natural biopolymers and synthetic plastics on the basis of both circular biofuel production and bioremediation st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 315 publications
0
4
0
Order By: Relevance
“…2 B). The active site of laccases consists of a type 1 (T1) copper site that catalyzed the substrate oxidation, and a trinuclear copper cluster (T2 and T3 coppers) where the oxygen is reduced (Jones and Solomon 2015 ; Rovaletti et al 2023 ). Residues involved in Cu ions coordination are conserved and identified by combining structural information and multiple sequence alignments (Figs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 B). The active site of laccases consists of a type 1 (T1) copper site that catalyzed the substrate oxidation, and a trinuclear copper cluster (T2 and T3 coppers) where the oxygen is reduced (Jones and Solomon 2015 ; Rovaletti et al 2023 ). Residues involved in Cu ions coordination are conserved and identified by combining structural information and multiple sequence alignments (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Laccases are able to catalyze the oxidation of a diverse array of chemical compounds including polyphenols, diamines and aromatic amines and inorganic ions. Consequently, they are employed in different processes including lignin valorisation, (bio) polymers degradation and water bioremediation (Riva 2006 ; Ostadhadi-Dehkordi et al 2012 ; Rovaletti et al 2023 ). Promoting the advancement of more sustainable processes involves expanding the range of substrates and applications for laccases, for instance, by combining these enzymes with aromatic molecules, creating the so-called laccase/mediator system (LMS) (Riva 2006 ; Morozova et al 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the present work provides new insights on the C–H oxidation mechanism by laccases, which can be generalized inspiring future theoretical/experimental investigations focused on hydrocarbons of different nature, such as other aromatic pollutants or plastics. 82…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, two excellent review articles have been reported on related topics. Arrigoni, Bertini, and coworkers have presented an overview of theoretical investigations for elucidating the mechanism of metalloenzymes involved in the degradation and valorization of natural biopolymers and synthetic plastics [ 8 ]. Further, Leone, Lombardi, and coworkers have described the most recent advances in the development of homogeneous hydrogen evolution catalysts envisioned to mimic hydrogenases [ 9 ].…”
mentioning
confidence: 99%